2014
DOI: 10.4103/0019-5154.135488
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of direct immunofluorescence in the diagnosis of immunobullous dermatoses

Abstract: Background:Autoimmune blistering diseases are a group of bullous disorders characterized by pathogenic antibodies directed at the target antigens, which are components of the desmosomes or adhesion complex at the dermoepidermal junction. Direct immunofluorescence (DIF) is invaluable in the diagnosis of these lesions.Aim:The aim of this study was to evaluate the sensitivity of DIF in immunobullous dermatoses and to study the pattern of DIF. The study also aims to correlate DIF with clinical and histologic findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
7
22
0
Order By: Relevance
“…This was in concordance to study by Buch et al which showed 100% of cases having granular IgA deposition at dermal papillae. 7 Present study showed 100% cases of PF having IgG deposition and 66.7% showing additional C3 deposition also. Study by Deepti et al showed 75% of cases having only IgG deposition and 25% having both IgG and C3 deposition.…”
Section: Type Of Antibodies Deposition On Dif In Vesiculobullous Lesionssupporting
confidence: 56%
See 3 more Smart Citations
“…This was in concordance to study by Buch et al which showed 100% of cases having granular IgA deposition at dermal papillae. 7 Present study showed 100% cases of PF having IgG deposition and 66.7% showing additional C3 deposition also. Study by Deepti et al showed 75% of cases having only IgG deposition and 25% having both IgG and C3 deposition.…”
Section: Type Of Antibodies Deposition On Dif In Vesiculobullous Lesionssupporting
confidence: 56%
“…6 Study by Buch et al described majority (18/25) of BP showing linear IgG and C3 deposition in the basement membrane zone (BMZ). 7 In our study 100% cases of DH showed IgA deposition and 20% of the cases showed additional C3 deposition. This was in concordance to study by Buch et al which showed 100% of cases having granular IgA deposition at dermal papillae.…”
Section: Type Of Antibodies Deposition On Dif In Vesiculobullous Lesionssupporting
confidence: 52%
See 2 more Smart Citations
“…In the case, that DIF is done during the treatment by immunosupresives, the results of DIF can be negative. Negative immunofl uorescence may be viewed as the state of immunological remission in pemphigus (26).…”
Section: Discussionmentioning
confidence: 99%